2018
DOI: 10.3389/fenvs.2018.00006
|View full text |Cite
|
Sign up to set email alerts
|

How Does Changing Pesticide Usage Over Time Affect Migrating Amphibians: A Case Study on the Use of Glyphosate-Based Herbicides in German Agriculture Over 20 Years

Abstract: Since its introduction in 1974, the use of glyphosate in agriculture has been continuously increasing; however, the application modes of this herbicide have been changing. Therefore, glyphosate-based herbicides can be used as an appropriate indicator for assessing how changes in pesticide application modes affect wild-living organisms in agricultural landscapes over time. Amphibians that migrate through arable fields may be exposed to the chemicals applied to field crops. Using data on the temporal coincidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The increasing boost after 1990 was clearly due to the worldwide introduction of GT crops, and this growth in consumption was further intensified with the expansion of the use of multiple trait (stacked genetic events) GM crops. Nonetheless, the use of glyphosate increased in regions without GM crop cultivation (due to pre-harvest or post-harvest chemical desiccation) as well: the overall consumption of glyphosate in Germany was boosted 5.7-fold between 1992 and 2012 (Berger et al, 2018). Thus, since 2012 glyphosate alone represented globally a stable 12% of the overall pesticide market and 13% of the market for synthetic pesticides (BCC Research, 2012;Transparency Market Research, 2014.…”
Section: The Worldwide Market Of Glyphosatementioning
confidence: 99%
“…The increasing boost after 1990 was clearly due to the worldwide introduction of GT crops, and this growth in consumption was further intensified with the expansion of the use of multiple trait (stacked genetic events) GM crops. Nonetheless, the use of glyphosate increased in regions without GM crop cultivation (due to pre-harvest or post-harvest chemical desiccation) as well: the overall consumption of glyphosate in Germany was boosted 5.7-fold between 1992 and 2012 (Berger et al, 2018). Thus, since 2012 glyphosate alone represented globally a stable 12% of the overall pesticide market and 13% of the market for synthetic pesticides (BCC Research, 2012;Transparency Market Research, 2014.…”
Section: The Worldwide Market Of Glyphosatementioning
confidence: 99%
“…Among them, Hallmann, Foppen, van Turnhout, de Kroon, and Jongejans (2014) linked the introduction of neonicotinoids to a negative trend in insectivorous bird populations by comparing different periods of surveys (before/after). Berger et al (2018) observed a relationship between changes in glyphosate application modes and amphibian migration. Finally, Seibold et al (2019) showed a general decline of arthropods driven by land-use intensification at large spatial extent.…”
Section: Introductionmentioning
confidence: 97%
“…Concomitantly, crop diversity decreased by more than 30% while the total crop coverage of land increased (Meyer et al 2013). These changes in agricultural practice had negative consequences on biodiversity, resulting in declining plant (Meyer et al 2013, Altenfelder et al 2014, bird (Donald et al 2006), invertebrate (Wilson et al 1999) and amphibian (Berger et al 2011(Berger et al , 2018 diversity. Furthermore, plant communities became homogenized (Macdonald andJohnson 2000, Baessler andKlotz 2006), as has commonly been observed after land-use intensification (Smart et al 2006).…”
Section: Introductionmentioning
confidence: 99%